Methods Innovation, Media and Evaluation on Vocabularies Learning in Boarding Classroom SMPIT LHI Yogyakarta - Khotimatun Nafi’ah; Abdul Latif (Jurnal Internasional Pendidikan Bahasa Arab, 2020)
This paper aims to give method, media and evaluation innovation in vocabulary learning at Arabic language class of LHI Junior High School Yogyakarta. The learning with same methods repeatedly will make the students not excited, so it need method, media and evaluation innovation in the learning for better learning quality and student achievement. The method of this research is using collect data from school with details interview and the author add some literatures as a reference. The methods innovation are using variation of methods in a week (4x30 minutes), and the methods is repetition words, direct method with contextual, games/singing, and reading or understanding. The medias innovation are using picture, real object/environment, video/film, and android aplication (games). And the last, the evaluations innovation are two kinds: speaking and writing, the students do an examination and memorize the vocabularies.